2022
DOI: 10.1155/2022/9505945
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction between the Characteristics of Retinal Microangiopathy and Risk Factors for Cerebral Small Vessel Disease

Abstract: Objective. This study was designed to explore the characteristics of retinal microangiopathy in patients with cerebral small vessel disease (CSVD) and clarify its interaction with the risk factors for CSVD. Methods. Sixty patients with CSVD and 15 healthy individuals were enrolled. Demographic data, risk factors, and medical history were recorded, and magnetic resonance imaging was performed to detect and analyze the characteristics of retinal microangiopathy in the two groups. The interaction among retinal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There is mounting evidence that retinal biomarkers are related to the emergence of various CSVD imaging features, which is important for the increased risk of cognitive impairment ( 20 , 34 ). It has been reported that the CSVD burden was associated with a wider CRVE, a smaller AVR, and a higher incidence of vessel tortuosity ( 35 ). A further study indicated that cerebral WMH might be partially predicted by non-invasive fundus photography via deep learning algorithm ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that retinal biomarkers are related to the emergence of various CSVD imaging features, which is important for the increased risk of cognitive impairment ( 20 , 34 ). It has been reported that the CSVD burden was associated with a wider CRVE, a smaller AVR, and a higher incidence of vessel tortuosity ( 35 ). A further study indicated that cerebral WMH might be partially predicted by non-invasive fundus photography via deep learning algorithm ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Previous studies of imaging markers of SVD-related injuries were mainly concentrated on the intracranial, including retinal microvascular diseases. 16 However, we are not aware of studies in which the imaging manifestations of SVD in spinal cord injuries have specifically been investigated. In fact, we are not aware of any reports of spinal cord SVD.…”
mentioning
confidence: 99%